The Embodiment of Architectural Experience: A Methodological Perspective on Neuro-Architecture - Wang, Sheng; Sanches de Oliveira, Guilherme; Djebbara, Zakaria; Gramann, Klaus (Frontiers in Human Neuroscience, 2022)
People spend a large portion of their time inside built environments. Research in neuro-architecture—the neural basis of human perception of and interaction with the surrounding architecture—promises to advance our understanding of the cognitive processes underlying this common human experience and also to inspire evidence-based architectural design principles. This article examines the current state of the field and offers a path for moving closer to fulfilling this promise. The paper is structured in three sections, beginning with an introduction to neuro-architecture, outlining its main objectives and giving an overview of experimental research in the field. Afterward, two methodological limitations attending current brain-imaging architectural research are discussed: the first concerns the limited focus of the research, which is often restricted to the aesthetic dimension of architectural experience; the second concerns practical limitations imposed by the typical experimental tools and methods, which often require participants to remain stationary and prevent naturalistic interaction with architectural surroundings. Next, we propose that the theoretical basis of ecological psychology provides a framework for addressing these limitations and motivates emphasizing the role of embodied exploration in architectural experience, which encompasses but is not limited to aesthetic contemplation. In this section, some basic concepts within ecological psychology and their convergences with architecture are described. Lastly, we introduce Mobile Brain/Body Imaging (MoBI) as one emerging brain imaging approach with the potential to improve the ecological validity of neuro-architecture research. Accordingly, we suggest that combining theoretical and conceptual resources from ecological psychology with state-of-the-art neuroscience methods (Mobile Brain/Body Imaging) is a promising way to bring neuro-architecture closer to accomplishing its scientific and practical goals.